CAPITAL INVESTMENT: TREATMENT AND REGULATION FOR ACCOUNTING AND AUDIT PURPOSES IN POST-WAR UKRAINE - HEVLYCH, Larysa; MAZURKEVYCH, Yelyzaveta (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Despite the considerable number of studies of capital investments, the question of the actual definition of this definition for the purposes of accounting and auditing, taking into account the post-war development of Ukraine, still remains open. The purpose of the article is to generalize the main problems of identification and legal regulation of capital investments for the purposes of their accounting and auditing from the point of view of finding ways to solve them. The article analyzes the interpretation of the term "capital investment" in the scientific debate, the international and domestic regulatory framework, and its influence on the organization of effective accounting and auditing. It was established that the definition of the concept of "capital investment" in national legislation is ambiguous, and it is absent in international accounting regulations, which creates a problem of managing capital investment at the enterprise level. To solve this problem, it is proposed to use definitions of capital investments from the point of view of economic interpretation and for accounting purposes. The work identifies the problems of capital investment management, for the solution of which the development of a standard is proposed, which will prescribe the elements of regulation at the state and enterprise levels. The presence of such regulation, on the one hand, will create confidence in the national economy on the part of external investors, on the other hand, it will allow to organize effective accounting, reliable reporting, and independent audit of capital investments of enterprises. The directions of further research are defined elements of the accounting policy in terms of accounting, internal control, and audit of capital investments, which will allow to take into account the peculiarities of the activities of domestic business entities.